Industrial training report: Putra Specialisti Hospital Melaka Sdn Bhd / Syamimi Wardah Ali - Ali, Syamimi Wardah (Faculty of Business and Management, 2025)
This internship reflection post discusses my 24-week Industrial Training (MGT666) internship at Putra Specialist Hospital, Melaka, from August 12, 2024, to January 24, 2025. This internship gives students hands-on instruction to complete employer-assigned tasks and obtain real-world experience. I hope to improve my practical skills, communication, and task completion with this chance. The report will start with Putra Specialist Hospital Melaka's background, vision, mission, organisational structure, and goods and services. I will also discuss my medical record trainee experience under Encik Fikri and assisting EMR professionals like Encik Syukery and Cik Diyanah. Furthermore, Puan Siti Aishah Binti Abd Gani Assistant Manager in Medical Records Department, mentored me during my internship. This program will equip me for professional life with its skills and perspectives. This report's second section will analyse the company's strengths, opportunity, weaknesses, and threats. This study will examine departmental issues and provide ways to str engthen, minimise, capitalise, and handle threats. The report will finish with documentation of my Medical Record Trainee participation and assignments performed.